2017
DOI: 10.3389/fimmu.2017.00589
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Complement C3 Gene Reveals Susceptibility to Severe Preeclampsia

Abstract: Preeclampsia (PE) is a common vascular disease of pregnancy with genetic predisposition. Dysregulation of the complement system has been implicated, but molecular mechanisms are incompletely understood. In this study, we determined the potential linkage of severe PE to the most central complement gene, C3. Three cohorts of Finnish patients and controls were recruited for a genetic case-control study. Participants were genotyped using Sequenom genotyping and Sanger sequencing. Initially, we studied 259 Finnish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 57 publications
(64 reference statements)
1
31
0
1
Order By: Relevance
“…Lokki et al performed a genetic case-control study, and discovered three SNPs within the C3 gene that were associated with severe preeclampsia [39]. These SNPs characterized a 16 nucleotide haplotype signature, in the highly conserved middle region of the maternal C3 gene, that could influence susceptibility to the disease.…”
Section: The Complement System In Stage 1 Of Placental Preeclampsiamentioning
confidence: 99%
“…Lokki et al performed a genetic case-control study, and discovered three SNPs within the C3 gene that were associated with severe preeclampsia [39]. These SNPs characterized a 16 nucleotide haplotype signature, in the highly conserved middle region of the maternal C3 gene, that could influence susceptibility to the disease.…”
Section: The Complement System In Stage 1 Of Placental Preeclampsiamentioning
confidence: 99%
“…It was speculated that these two SNPs may represent different tagging SNPs for an unknown causal SNP 30 . Interestingly, in a recent study the rs223005 was shown to be associated with severe PE 18 .…”
Section: Scientific Reports |mentioning
confidence: 93%
“…The exons including flanking intronic regions were sequenced using standard Sanger sequencing. We used primers for C3 as previously reported 18 . The primers used for factor H and CD46 are listed in Supplemental Tables 1 and 2.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro data also suggest that mutations in FOXD1, a transcription factor that directly seems to target C3, leading to both decreased and increased C3 expression, were deleterious (17). Genetic variants in the C3 gene have also been reported to be associated with severe preeclampsia (18). Thus, C3 appears to have an important physiological role in the early phase of pregnancy and in placental development and a subtle fine-tuning of the C3 level is necessary for optimal function.…”
mentioning
confidence: 99%